Climate change and renewable energy : national policies and the role of communities, cities and regions (International Renewable Energy Agency, 2019)
The transformation of the global energy system to reduce carbon dioxide (CO2) emissions requires engagement at all levels of society - from communities, regions and governments to numerous other stakeholders across the public and private sectors. This report examines ways for Group of Twenty (G20) countries to mobilise effective, meaningful action on energy decarbonisation. Japan, holding the G20 presidency in 2019, asked the International Renewable Energy Agency (IRENA) for a report on the implications of the global energy transformation for climate and sustainability in a broad sense. Along with preserving the environment, improving urban air quality, and protecting the world's climate, the massive uptake or renewables and energy efficiency promises to bring financial and economic opportunities, wider prosperity and new jobs. IRENA has engaged with successive G20 presidencies since 2015 on a toolkit for renewable energy deployment. Increasingly, the organisation has aligned its G20 toolkit with the Paris Agreement and explored investment implications.